2016
DOI: 10.1016/j.jvs.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Renal dysfunction and the associated decrease in survival after elective endovascular aneurysm repair

Abstract: Objective The reported frequency of renal dysfunction after elective endovascular aneurysm repair (EVAR) varies widely in current surgical literature. Published research establishes pre-existing end-stage renal disease as a poor prognostic indicator. We intend to quantify the mortality effect associated with renal morbidity developed postoperatively and to identify modifiable risk factors. Methods All elective EVAR patients with preoperative and postoperative renal function data captured by the Vascular Qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 40 publications
2
37
0
1
Order By: Relevance
“…Developing CIN results in worse treatment outcomes related to mortality, serious morbidity, and myocardial infarction after PCI (15). Postoperative renal dysfunction after EVAR has been reported to be associated with decreased estimated long-term survival (7). Additionally, this study demonstrated that CIN immediately after EVAR was associated with more hospital deaths and worsened 1-year mortality.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Developing CIN results in worse treatment outcomes related to mortality, serious morbidity, and myocardial infarction after PCI (15). Postoperative renal dysfunction after EVAR has been reported to be associated with decreased estimated long-term survival (7). Additionally, this study demonstrated that CIN immediately after EVAR was associated with more hospital deaths and worsened 1-year mortality.…”
Section: Discussionmentioning
confidence: 64%
“…It is associated with a longer hospital stay, renal impairment, and higher mortality (5,6). Zarkowsky et al (7). reported that postoperative renal dysfunction after EVAR was associated with decreased estimated long-term survival.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Postoperative AKI is a common, but serious, complication of aortic repair for AAA because it may increase early mortality 8,9) and patients hospital stay 10,11) ; it may also affect late survival. 8,12,13) Although much attention to date has been given to this complication, research into AKI following AAA repair remains challenging due to the fact that AAAs differ from each other morphologically and clinically. For example, some aneurysms are ruptured and some unruptured, and some involve visceral vessels whereas others do not.…”
Section: Introductionmentioning
confidence: 99%
“…5 While many studies have reported satisfactory results of this less invasive procedure, the long-term outcomes of EVAR, specifically, the effect of aortic stent wires on renal blood flow and subsequent renal function is still a main concern to clinicians when evaluating the durability of this technique. [6][7][8][9][10] AAA patients treated with EVAR have regular imaging surveillance to determine whether the aortic aneurysm is successfully excluded, the stent-graft is position properly in relation to the aortic branches, and the renovisceral arteries are patent. Computed tomography angiography (CTA) is currently the reference imaging modality for follow-up of EVAR.…”
Section: Introductionmentioning
confidence: 99%